Reference optical turbulence and wind profiles for single conjugate and extreme adaptive optics. Issue 2 (7th October 2022) - Farley, O J D
ABSTRACT: We present a simple method of extracting a small number of reference optical turbulence and wind profiles from a large data set for single conjugate and extreme adaptive optics (AO) simulations. These reference profiles can be used in slow end-to-end AO simulations to represent the variability of the atmosphere. The method is based on the assumption that performance for these systems is correlated with integrated atmospheric parameters r 0, θ0, and τ0 . Profiles are selected from a large data set that conforms concurrently to the distributions of these parameters, and hence represents the variability of the atmosphere as seen by the AO system. We also extend the equivalent layers method of profile compression to include wind profiles. The method is applied to stereo-SCIDAR data from ESO Paranal to extract five turbulence and wind profiles that cover a broad range in atmospheric variability, and we show using analytical AO simulation that this correlates to the equivalent range of AO-corrected Strehl ratios.